UPAYA MENINGKATKAN MINAT BELAJAR SISWA MELALUI PENGGUNAAN MEDIA AUDIO VISUAL PADA MATA PELAJARAN BAHASA INDONESIA KELAS 2 DI SDN DUPAK 1 SURABAYA - Rahma Elvira; Roni Rodiyana; Dwi Natalia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to increase students' learning interest in Grade II students at SDN Dupak 1 Surabaya. The subjects of this study were 24 Grade II students. The method used was classroom action research. Data collection was conducted using instruments, observation, interviews, and documentation. The results showed that in Cycle I, the average score of learning interest was 78.67, and in Cycle II, it was 84.75. These results indicate a change, with an increase in the average score from 78.67 to 84.75. The researcher targeted a final average score of 80 by the end of the cycle, and the result exceeded 80, meaning that students' learning interest improved significantly. Qualitative analysis results demonstrated that the use of audiovisual media could enhance students' learning interest. Students were able to focus their attention throughout the learning activities. They participated in the learning process with joy, enthusiasm, and energy. Therefore, it can be concluded that audiovisual media can increase the learning interest of Grade II students at SDN Dupak 1 Surabaya.